Periodismo fotográfico y su efecto en la difusión de los géneros periodísticos del diario aldia.com.ec, año 2022 - Carbo Macías, Maholy Nicole (2022)
Journalism dates back to the fifteenth century, the invention of the printing press brought with it the development and evolution of what we know today as journalism, and the genres that have developed through it. Photojournalism dates back to the first wars in the world and its documentation through photographs that show what is raised and is recorded for the memory. For this reason, the general objective of this research lies in investigating the effect of photographic journalism on the journalistic genres of the Aldia newspaper, during the year 2021. To obtain this information, interviews were conducted with those involved, maintaining a focus group of around 20 people, in order to collect first-hand information. For this reason, the general objective of this research was concluded through the information collected that photographic journalism in each of its genres provides a broad view of the news in development prior to reading it, this being a guide, a preamble that directly transmits the information, photographic journalism is of the utmost importance in the dissemination of each given journalistic genre, since in those the information that is intended is reflected